Infecção em idosos internados em instituição de longa permanência - Bôas, Paulo José Fortes Villas [UNESP]; Ferreira, Ana Lúcia Dos Anjos [UNESP] (My University, 2007)
OBJECTIVE. To evaluate the occurrence of infection in elderly interned in long-term care facilities (LTCF) during 13 consecutive months. METHODS. Fifty five elderly were evaluated according to infection and, reporting was standardized. RESULTS. The median age was 75 (66 - 81) years. The data set consisted of 20,896 patients-day (PD) of care during the period, with a total of 76 infections for a pooled mean rate of infections 3.20 per 1,000 PD of care. Patient infection rate was 63.6%. Prevalent topographies of infection were respiratory (50%), urinary tract (32%), skin and soft tissue (12%) and gastroenteritis (7%), with an infection rate for specific categories/1000 PD of 1.60, 1.01, 0.38, 0.21, respectively. Mortality infection rate was 5%. Microbiological agents were isolated in 30.5% of the infection episodes. Escherichia coli and Staphylococcus aureus were prevalent. CONCLUSION. Infection presented an elevated incidence in the elderly interned, but no unusual problem with infections was disclosed.
Infection in elderly interned in long-term care facilities
Keywords: Elderly; Epidemiology; Infection; Long-term care facilities